2001
DOI: 10.1128/aem.67.3.1116-1122.2001
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Driven Adaptation of the Bacterial Community in Peat Measured by Using Thymidine and Leucine Incorporation

Abstract: The temperature-driven adaptation of the bacterial community in peat was studied, by altering temperature to simulate self-heating and a subsequent return to mesophilic conditions. The technique used consisted of extracting the bacterial community from peat using homogenization-centrifugation and measuring the rates of thymidine (TdR) or leucine (Leu) incorporation by the extracted bacterial community at different temperatures. Increasing the peat incubation temperature from 25°C to 35, 45, or 55°C resulted in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 38 publications
4
43
0
Order By: Relevance
“…The presence of Ktedonobacterialike taxa in Bare cinders is consistent with results from Ranneklev and Bååth (2001), which indicate that fluctuating thermal regimes can select for and maintain thermophilic or thermotolerant communities simultaneously with mesophilic communities.…”
Section: Introductionsupporting
confidence: 75%
See 2 more Smart Citations
“…The presence of Ktedonobacterialike taxa in Bare cinders is consistent with results from Ranneklev and Bååth (2001), which indicate that fluctuating thermal regimes can select for and maintain thermophilic or thermotolerant communities simultaneously with mesophilic communities.…”
Section: Introductionsupporting
confidence: 75%
“…Several previous studies (Ranneklev and Bååth, 2001;Pettersson and Bååth, 2003;Hartley and Hopkins, 2008;Bárcenas-Moreno et al, 2009) have demonstrated that soil microbial communities can adapt to elevated temperature regimes. For example, using growth rate as a variable, Ranneklev and Bååth (2001) have shown that heating peat soil from 25-55 1C resulted in community adaptation with optimal growth at 55 1C in only 3 days.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As previously reported (Bárcenas-Moreno et al, 2009;Hamdi et al, 2013;Ranneklev and Bååth, 2001), the varying temperature regime (V T ) can promote the optimal growth of most mesophilic microbial groups. In addition, highly diversified microbial pathways increase the exploitation of C resources and the size of the labile C pool (Bracho et al, 2016;Sun et al, 2016).…”
Section: Temperature Regimementioning
confidence: 73%
“…Furthermore, the temperature sensitivity of C mineralization not only varies in those kinetic properties, which are partially determined by soil properties , but also changes with environmental conditions, such as constant vs. varying temperature regimes (Conant et al, 2008;Fang et al, 2005;Nakajima et al, 2016;Xia et al, 2009;Zhu and Cheng, 2011), the aeration statuses (Blagodatskaya et al, 2014;Devêvre and Horwáth, 2000;Diakova et al, 2016), the forest stands (Guo et al, 2016;Gutiérrez-Girón et al, 2015;Rey and Jarvis, 2006), and the soil horizons (Laganière et al, 2015;Xu et al, 2014). These constraints, especially the temperature and the aeration status, are fixed as constant in most studies, and a continuously changing vs. constant environmental comparison has rarely been scrutinized (Conant et al, 2008;Hartley et al, 2008;Pettersson and Bååth, 2003;Ranneklev and Bååth, 2001).…”
Section: Introductionmentioning
confidence: 99%